Unconscious processing of prototype heuristics in scientific innovation problem-solving - Ling, Yushi; Tan, Liu; Zhang, Liyi; Cao, Guikang (Frontiers in Psychology, 2023)
Previously published studies on the effect of how do different levels of unconsciousness (UC) and different loads of executive functions (EFs) affect insight problem solving are not consistent. In a set of three experiments, we sought to figure out how different levels of UC affect different levels of difficulty problem solving, and what role does EFs play? To test it, we used scientific innovation problems (SIP) as insight metrics and used distractor tasks to induce UC. Experiment 1 confirmed that compared with conscious processing, unconscious processing is more conducive to obtaining prototype heuristics for correctly solving creative problems. Experiment 2 furthermore found that different levels of unconscious processing, which were induced by different distractor tasks, made a different impact on high or low difficulty creativity problem solving. Experiment 3 indicated that unconscious processing could improve prototype activation and the ability to use key heuristics information in the prototype heuristics processing, by improving the working memory, inhibitory control, and shifting ability of EFs. Overall, the present results are significant in providing more evidence for the role of conscious levels in insight problem solving.